Four new bdelloid rotifers from Korea - Song, Min Ok; Lee, Chang-Ho (Zootaxa, 2019)
The bdelloid rotifers from terrestrial habitats and a wetland at six different locations in Korea were studied. The study resulted in 17 new Korean records and 4 new species, Philodina corrugata n. sp., P. triangularis n. sp., P. tumidipes n. sp., and Macrotrachela quadricaudata n. sp. Among the 17 new Korean records, 15 species are new to Asian fauna as well and include eight rare species with poorly known distributions. Habrotrocha alacris Milne, H. cucullata Murray, H. quinquedens doornensis De Koning, Macrotrachela induta Donner, Mniobia edmondsoni Burger, and Mniobia lineata Rahm have been reported only from two to three countries including their type localities before the present study. Our study is the first to report Macrotrachela ligulifera Bartoš and M. obtusa Haigh outside their type localities. The descriptions of the four new species and brief discussions on some of the rare species are provided here. In addition, a partial sequence of mitochondrial cytochrome c oxidase subunit I gene (mtCOX1) for P. corrugata n. sp. is presented.